(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
In the article we are talking about the personal role-play positions of a modern student-psychologist. The basic theoretical positions are determined and features of roles in society are characterized. A study was carried out to identify the actual roles and compared the importance of the personal and professional sphere of a modern student-psychologist.